1988
DOI: 10.1007/bf03392462
|View full text |Cite
|
Sign up to set email alerts
|

Matching Theory in Natural Human Environments

Abstract: Matching theory is a mathematical account of behavior, many aspects of which have been confirmed in laboratory experiments with nonhuman and human subjects. The theory asserts that behavior is distributed across concurrently available response alternatives in the same proportion that reinforcement is distributed across those alternatives. The theory also asserts that behavior on a single response alternative is a function not only of reinforcement contingent on that behavior, but also of reinforcement continge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
154
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(162 citation statements)
references
References 39 publications
3
154
0
5
Order By: Relevance
“…Both the "real world" and tightly controlled experimental settings consist of countless reinforcement alternatives for any organism at any given time (McDowell, 1988). Put another way, it may be shortsighted to simply assume that choice is limited to two options, as is dictated by Equations 1 and 2, and in cases where only one target behavior is concerned, a single-alternative matching theory is necessary.…”
Section: Herrnstein's Hyperbolamentioning
confidence: 99%
See 1 more Smart Citation
“…Both the "real world" and tightly controlled experimental settings consist of countless reinforcement alternatives for any organism at any given time (McDowell, 1988). Put another way, it may be shortsighted to simply assume that choice is limited to two options, as is dictated by Equations 1 and 2, and in cases where only one target behavior is concerned, a single-alternative matching theory is necessary.…”
Section: Herrnstein's Hyperbolamentioning
confidence: 99%
“…The single-alternative matching equation has been used to document numerous instances of matching in the natural environment (see McDowell, 1988). In one example, McDowell (1988) demonstrated that Equation 5 accounted for a young boy's rate of self-injurious behavior, with reprimands serving as the presumed maintaining consequence.…”
Section: Herrnstein's Hyperbolamentioning
confidence: 99%
“…Responding to the schedule of reinforcement and the video disrupter will reflect the amount of reinforcement from these sources. If there is an alternative source of reinforcement available, responding should match the two available alternatives for responding based on the amount of reinforcement of those two alternatives (McDowell, 1988). This could be achieved in future research by having all subjects answer questions about the television shows they have watched and to award points exchangeable for money for the answers.…”
Section: Further Research On Reinforcement Historiesmentioning
confidence: 99%
“…The matching law may also be expressed mathematically as follows: where R 1 represents the rate of Response 1, R 2 represents the rate of Response 2, r 1 represents the reinforcement rate for R 1 , and r 2 represents the reinforcement rate for R 2 . A number of basic and applied studies on choice have shown that both nonhuman and human behavior generally conform to the relation described by the matching equation when reinforcement schedules are precisely controlled (Baum, 1979;Davison & McCarthy, 1988;Mace, Neef, Shade, & Mauro, 1994;McDowell, 1988;Neef & Lutz, 2001;Neef, Mace, & Shade, 1993). In addition, transformations of Equation 1 allow the incorporation of additional variables known to influence response allocation, such as mag-nitude of reinforcement, quality of reinforcement, delay to reinforcement, and duration of reinforcement (Baum, 1974b).…”
mentioning
confidence: 99%